The effect of exercise on sleep in adults with type 1 diabetes. Issue 2 (14th September 2017) - Reddy, Ravi; El Youssef, Joseph; Winters‐Stone, Kerri; Branigan, Deborah; Leitschuh, Joseph; Castle, Jessica; Jacobs, Peter G.
Abstract : The aim of this pilot study was to investigate the effect of exercise on sleep and nocturnal hypoglycaemia in adults with type 1 diabetes (T1D). In a 3‐week crossover trial, 10 adults with T1D were randomized to perform aerobic, resistance or no exercise. During each exercise week, participants completed 2 separate 45‐minutes exercise sessions at an academic medical center. Participants returned home and wore a continuous glucose monitor and a wrist‐based activity monitor to estimate sleep duration. Participants on average lost 70 (±49) minutes of sleep ( P = .0015) on nights following aerobic exercise and 27 (±78) minutes ( P = .3) following resistance exercise relative to control nights. The odds ratio with confidence intervals of nocturnal hypoglycaemia occurring on nights following aerobic and resistance exercise was 5.4 (1.3, 27.2) and 7.0 (1.7, 37.3), respectively. Aerobic exercise can cause sleep loss in T1D possibly from increased hypoglycaemia.